MOTIVASI PENGUNJUNG DI PUSAT LATIHAN GAJAH (PLG) MINAS KABUPATEN SIAK - ", Nurfitriana; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is to find the motives that influenced tourist to visit Pusat Latihan Gajah (PLG) Minas Siak district.This research uses descriptive methods to analyze problem which is going to conducted. The sample of the data collection techniques on this reseach the writer using liker scale as an instrument to measuring the lenght of intervals that can be used to find quantitative data. The sample of this research was 100 people were taken by using accidental sampling.Based on the research are the influence of the phusical motive get 1.625 scores, culture motive get 859 scores, social motive get 1.484 scores and fantasy motive get 1.292 scores.Keyword: Motivation, Pusat Latihan Gajah Minas, tourist